Perceived Parenting Styles Predicting Obsessive Compulsive Personality Traits in Students and Obsessive-Compulsive Disorder in Patients - Fazal, Basla; Zahra, Syeda Mehreen (Journal of Pakistan Psychiatric Society, 2021)
ObjectivePresent study was aimed to discover common perceived parenting style behind OCD and OCPTs and the association of perceived parental rearing method with OCPTs and OCD symptom dimensions.Study DesignCorrelational Research DesignPlace and Duration of StudyStudy was completed in duration of six months in Lahore.Subjects and MethodsWork was done on two samples and results of both samples were analyzed separately. Sample I included 100 students aged between 18 to 24 years (M =21.49, SD =2.31) while sample II included 100 diagnosed OCD patients (M=30.57, SD=5.58). Parental Authority Questionnaire (PAQ; Buri, 1989) 30 item and FFOCI-SF consisting of 48-item self-report questionnaire (Samuel et al., 2012) was used.ResultsRegression analysis of sample I revealed that paternal permissiveness negatively predicts excessive worry, detached coldness, risk aversion, constricted, inflexible, dogmatism, perfectionism, fastidiousness, punctiliousness, workaholism, doggedness and ruminative deliberation. Paternal authoritarianism positively predicts all the twelve OCPTs. Paternal authoritativeness negatively predicts detached coldness and inflexible. It also showed that maternal permissiveness negatively all the twelve OCPTs. Maternal authoritarianism positively predicts excessive worry, detached coldness, risk aversion, constricted, inflexible, dogmatism, perfectionism, workaholism, doggedness and ruminative deliberation while maternal authoritativeness negatively predicts detached coldness, risk aversion, inflexible, doggedness and ruminative deliberation. Spearman Rank Order Correlation of sample II showed that no significant relationship of paternal and maternal parenting style with specific symptom dimension of OCD was found.ConclusionAuthoritarian parenting style positively predicts OCPTs. No significant relationship exists between perceived parenting style and specific OCD symptom dimensions.